Public Reason, Bioethics, and Public Policy: A Seductive Delusion or Ambitious Aspiration? - Fleck, Leonard M. (Cambridge quarterly of healthcare ethics, 2025)
Can Rawlsian public reason sufficiently justify public policies that regulate or restrain controversial medical and technological interventions in bioethics (and the broader social world), such as abortion, physician aid-in-dying, CRISPER-cas9 gene editing of embryos, surrogate mothers, pre-implantation genetic diagnosis of eight-cell embryos, and so on? The first part of this essay briefly explicates the central concepts that define Rawlsian political liberalism. The latter half of this essay then demonstrates how a commitment to Rawlsian public reason can ameliorate (not completely resolve) many of the policy disagreements related to bioethically controversial medical interventions today. The goal of public reason is to reduce the size of the disagreement by eliminating features of the disagreement that violate the norms of public reason. The norms of public reason are those norms that are politically necessary to preserve the liberal, pluralistic, democratic character of this society. What remains is reasonable disagreement to be addressed through normal democratic deliberative processes. Specific issues addressed from a public reason perspective include personal responsibility for excessive health costs, the utility of a metaphysical definition of death for organ transplantation, and the moral status of excess embryos generated through IVF and/or their use in medical research.